Internet of Things (IoT): Real-Time Monitoring for Decision Making Among The Malaysian Contractors - Hong Cing Cing,; Nur Syaimasyaza Mansor, (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2023)
The complexity of construction projects and the poor decision-making process often result in cost and time overruns. With the rapid growth of Industrial Revolution (IR4.0) in Malaysia, Internet of Things (IoT) is being expanded in the construction industry to improve project efficiency and performance. One of the benefits of IoT is it provides a real-time monitoring function to ensure that the construction players can access accurate data and information at the exact time throughout the project life cycle and assist in their decision making. Most studies have focused on how decision making is aided through the application of IoT during the design phase, with few studies focusing on the construction phase, particularly from the perspective of contractors. Without IoT, contractors need to use their professional experiences and limited data to make their decisions. As the contractors have to make a lot of decisions during the construction phase, the adoption of IoT can help the contractors to make fast and precise decisions. Despite its benefits, the adoption of IoT in the Malaysian construction industry is still low. With the focus on Grade 7 (G7) contractors in Malaysia, this paper intends 1) to study the types of IoT-based real-time monitoring technologies for decision-making among the contractors, and 2) to explore the potential improvements of decision making by the contractors after the adoption of IoT. The research adopted the qualitative method via semi-structured interviews. Based on the findings, there are 10 types of IoT-based real-time monitoring technologies being used and they have been utilised in several areas e.g. machineries and equipment, materials, labours, project sequences, waste management, risk management, productivity and quality of works, cost control and environmental protection. The function of the real-time monitoring of IoT such as the real-time data and report, sudden changes reporting, agentless real-time monitoring, root cause analysis, alerts and warnings and predictions, help the contractors in making their decision timely and accurately. Finding reported herein is considered significant towards raising industry players' awareness and acceptance of IoT in construction projects, thereby improving project efficiency and performance.